Credit and Exchange Rate-Based Stabilization - Khamis, May. (Washington, D.C. : International Monetary Fund, 1996)
This paper examines the behavior of private sector credit in chronic inflation countries that undergo exchange rate-based inflation stabilizations. It concludes that these programs are characterized by a strong increase in private sector credit, both in absolute terms and as a fraction of real economic activity. Empirical results using data for Mexico, Chile, Argentina, and Israel support a negative statistically significant relationship between credit and inflation for Mexico, Argentina, and Chile, but not for Israel. In addition, for both Chile and Mexico, dummy variables representing periods of inflation stabilization are positive and statistically different from zero indicating a stronger expansion in private sector credit during stabilization. These results could potentially explain the consumption boom that is usually present in the early stages of these programs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet